One step ahead of the plow: Using cropland conversion risk to guide Sprague's Pipit conservation in the northern Great Plains. (November 2015) - Lipsey, Marisa K.; Doherty, Kevin E.; Naugle, David E.; Fields, Sean; Evans, Jeffrey S.; Davis, Stephen K.; Koper, Nicola
Abstract: Rapid expansion of cropland threatens grassland ecosystems across western North America and broad-scale planning can be a catalyst motivating individuals and agencies to accelerate conservation. Sprague's Pipit ( Anthus spragueii ) is an imperiled grassland songbird whose population has been declining rapidly in recent decades. Here, we present a strategic framework for conservation of pipits and their habitat in the northern Great Plains. We modeled pipit distribution across its million-km 2 breeding range in Canada and the U.S. We describe factors shaping distribution, delineate population cores and assess vulnerability to future grassland losses. Pipits selected landscapes with a high proportion of continuous grassland within a relatively cool, moist climate. Sixty percent of the global breeding population occurred in Canada and 63% of the U.S. population occurred in Montana. Populations were highly clumped, with 75% of birds within 30% of their range. Approximately 20% of the population occurred on protected lands and over half used lands that were unlikely to be cultivated given current technologies. A quarter of pipits relied on remaining arable grasslands and potential population losses varied from 2–27% across scenarios. Most of the population (70%) was dependent on private lands, emphasizing the importance of voluntary approaches that incentivize good stewardship. Our maps depicting core populations and tillage risk enable partners to target conservation in landscapes where pipits will benefit most. Highlights: We modeled breeding distribution of Sprague's Pipit (Anthus spragueii) and overlaid cropland expansion predictions to assess future risks. Populations are concentrated in contiguous grasslands within a cool, moist climate envelope. Risk to populations from cropland expansion range from 2-27% across planning scenarios. Privately-owned lands support 70% of the breeding population. Conservation of Sprague's Pipit depends upon a systematic approach that invests heavily in private land partnerships.